Evaluation of Helicobacter pylori vacA genotype in Japanese patients with gastric cancer. - Shimoyama, T (1998)
AIM: To examine the vacA genotypes of Helicobacter pylori strains in Japan and to define whether any specific genotype was associated with gastric cancer. METHODS: The allelic variation of vacA gene was studied using a recently introduced polymerase chain reaction based vacA genotyping system. RESULTS: 80 H pylori strains were isolated from gastric biopsies of 40 patients with gastric cancer and 40 control subjects in a Japanese population. All strains were s1/m1 subtype and 79 of 80 strains were classified as s1a subtype. CONCLUSIONS: The recently proposed vacA genotyping system is applicable to Japanese H pylori strains and most strains have the s1a genotype, associated with increased virulence. While the high frequency of s1a/m1 vacA genotype might play a role in the increased incidence of atrophic gastritis and gastric cancer in Japanese subjects, it precludes its use as a predictor of clinical outcome of H pylori infection in Japan.